Cafeteria food payment system using QR code - Mohd Razif Izany, Mohd Nasaruddin (2018)
Financial management is one of the important things for everyone, especially among students. Most teens have problems managing their money, especially when they are in higher education. Adolescents are faced with a shortage of spending money because they are not skilled in managing their money properly, insufficient savings, or purchase of essentials and learning materials that exceed their estimated purchases. Payment by using the system QR codes has been raised to help the adolescents in managing their spending money better called the Cafeteria Food Payment System or the CFPayment system. This system works to help the adolescents in managing their spending money virtually so that they have saved on their spending before they face inadequate money for spending. In addition, the system also helps students in exile in terms of purchasing and spending. The objective of the system is to help adolescents manage money more efficiently, preventing them from having enough money for their expenses and their money left behind or forgetting to be removed from ATM machines. So to solve this problem, it has been proposed to be developed to meet the recommendations put forward to assist the youth in the management of their spending money more regularly and systematically. The expected result of this system is that the teens can manage their spending money better in order to avoid spending money problems they faced during their lessons in nature at a higher level.